A review of international trade and investment agreements and nutrition policy space in the Pacific - Bunkley, Noah; McCool, Judith; Garton, Kelly (Frontiers in Nutrition, 2023)
Small Island Developing States (SIDS) in the Pacific are heavily reliant on imported foods which are often nutritionally deficient, and typically high in salt, fat, and sugar. To curb nutrition-related noncommunicable diseases, nutrition policies are needed to create food environments that promote healthy diets. However, international trade and investment agreements (TIAs) may interfere with the policy space for SIDS to regulate their food environments by requiring member states to meet trade obligations that could conflict with their nutrition policy goals. In this review, we identify real examples of where TIAs have been responsible for changes in Pacific SIDS' nutrition policies alongside the potential for further constraints on healthy nutrition policies from Pacific Island participation in TIAs. In addition, we note the effects of regulatory chill from TIA obligations in Pacific SIDS, whereby healthy nutrition policies are not considered, developed, or implemented due to the threat of trade disputes or the complexity of TIA procedural requirements. Existing literature indicates that TIAs have shaped nutrition policies to fit within the global trade paradigm despite SIDS' nutrition policy imperatives. More can be done locally, regionally, and internationally to increase the importance of nutrition in the trade agenda, leverage regional institutions to champion nutrition regulation and support SIDS in navigating the trade and nutrition policy environment.